Panax ginseng and Salvia miltiorrhiza supplementation during eccentric resistance training in middle-aged and older adults: A double-blind randomized control trial. (December 2016) - Lin, Hsin-Fu; Chou, Chun-Chung; Chao, Hsiao-Han; Tanaka, Hirofumi
Highlights: Eccentric resistance training did not affect vascular functions in older adults. Chinese herbs did not modulate antioxidant and inflammatory adaptations. Chinese herbs may interfere with resistance training adaptations. Abstract: Background: Muscle damage induced by an acute bout of eccentric exercise results in transient arterial stiffening. In this study, we sought to determine the effects of progressive eccentric resistance exercise training on vascular functions, and whether herb supplementation would enhance training adaptation by ameliorating the arterial stiffening effects. Methods: By using a double-blinded randomized placebo-controlled design, older adults were randomly assigned to either the Panax ginseng and Salvia miltiorrhiza supplementation group (N = 12) or the placebo group (N = 11). After pre-training testing, all subjects underwent 12 weeks of unilateral eccentric-only exercise training on knee extensor. Results: Maximal leg strength and muscle quality increased in both groups (P<0.05). Relative increases in muscle mass were significantly greater in the placebo group than in the herb supplement group. Eccentric exercise training did not elicit any significant changes in muscle damage, oxidative and inflammatory biomarkers. There were no significant changes in blood pressure or endothelium-dependent vasodilation. None of the measures of arterial stiffness changed significantly with eccentric resistance training in both groups. Conclusions: These results suggest that Chinese herb supplementation does not appear to modulate vascular, and inflammatory adaptations to eccentric exercise training in middle-aged and older adults. However, Chinese herb supplementation abolished the increase in muscle mass induced by eccentric resistance training. (Trial registration: ClinicalTrials.gov: NCT02007304. Registered Dec. 5, 2013)